Beyond Deliberative Systems: Pluralizing the Debate. Issue 1 (1st June 2022) - Unknown
Abstract : Normative democratic theory with a focus on civic engagement is increasingly interested in how participatory instances connect into democratic systems (Dean, Rinne, et al. 2019; Elstub et al. 2018). The deliberative perspective has pioneered this debate and proposes a systemic view that observes how everyday talk and media discourses connect deliberative forums including parliaments, mini-publics, and protest formations (Mansbridge 1999; Mansbridge et al. 2012). While various approaches within the deliberative systems debate can be differentiated (Owen and Smith 2015), they commonly understand deliberative qualities as distributed within a broader system and focus on scaling up democratic deliberation through the transmission from the public to state institutions (Chambers 2012; Dryzek 2009).